Transmisión por semilla y control de la antracnosis del caupí,causada por Colletotrichum dematium, (Pers. ex Fr) Grove. (1990)
Seed transmission of Colletotrichuin dematiuin through cowpea seeds, and its control with fungicide seed treatments was studied at the Turipaná National Research Center of ICA (Colombian Institute of Agriculture) located in Cereté (Córdoba). Two out of eight genotypes tested showed significantly higher (a = 0.01) seed infection levels; they also exhibited higher seed transmission rates of C. de,natiuin. Treatment of infected seeds of line Licatur-1 with Benomyl (Benlate WP50, 3.0 gr/kg of seed) caused a significant reduction of seed infection levels (a = 0.01), and resulted in comparable decreases in anthracnose incidence, measured 24 days after seedling emergence in sand germinators. The effect of seed lot, soil type and fungicide seed treatment on anthracnose incidence was also evaluated. Results indicated a highly significant effect of seed lots, partially explained by environmental and seed crop management variations. Anthracnose incidence, decreased when the seeds were planted in a clay loam soil as compared to disease incidence in sand. Seed treatment with benomyl (Benlate WP50, 2.5 .3.0 gr/kg) or Mancozeb (Dithane M-45, 5.0 yr/kg) caused a significant reduction in anthracnose incidence. These results suggest that fungicide seed treatment is an effective control practice to prevent spread of C. de,natiu,n through cowpea seeds.